The Impact of Working Conditions on Academic Staff Turnover at Africa University, Mutare, Zimbabwe - Bigirimana, Stanislas; Sibanda, Esnath Ntombizodwa; Masengu, Reason (Asian Journal of Social Sciences and Management Studies, 2016)
A study was carried out to assess the impact of staff working conditions on academic staff turnover at Africa University, Mutare, Zimbabwe. Out of a total of 74 academic staff, a sample size of 35 was randomly selected in the four categories of lecturer, senior lecturer, associate professor and professor. Several facets of working conditions were explored, namely, leadership style, perceived organizational support, performance management system, academic freedom, collegiality, opportunity and support for research activities, workloads and psychological contracts. This study found that the working conditions were unfavorable and this led to situations where academic staff leaving Africa University at the earliest opportunity.